Some features of marine dynamics caused by damrey typhoon (11/2017) and its impacts on coral reef in Ninh Van waters, Khanh Hoa province - Long, Bui Hong; Chung, Tran Van; Thu, Phan Minh; Y., Latupov (Vietnam Journal of Marine Science and Technology, 2020)
Typhoon Damrey (Vietnamese name is Typhoon No.12 in 2017) landed in South Phu Yen - North Khanh Hoa provinces in the morning of 4th Nov 2017 causing severe damage to people, material and serious consequences on the social and economy of the region (especially Khanh Hoa Province). So far, there have been no published papers and reports on the results of analysis of observing and monitoring data, calculations on marine dynamics as well as their impact on some marine ecosystems. Based on the results of coral reef survey in the study area before and after storm as well as hydrodynamic model results, the paper presents some results of data analysis of monitoring water level, calculations of wave field, currents caused by Damrey Typhoon in coastal waters of Khanh Hoa Province. On that basis, there have initial comments on the impact of storm on the coral reef of this region for management, forecasting and mitigation of local natural disaster damage in the future